Fundamentos epistemológicos da museologia: uma proposta ao problema curricular - Nazareth, Gilson do Coutto (1991)
We wish to answer in the present work the following questions: what is Museology? What distinguishes Museology among the related disciplines in the same knowledge field? Which are Museology's epistemological foundations? And finally, why has Museology become such a technical subject in Brazil? (A fact that ends up by excluding museologists from managerial positions in their own area.). The educational question is embedded into the epistemological question. We' consider our main subject through several different aspects; one might even call them 'successive visions': the way museological education at the college level appears in the midst of its historical circumstances; the ideology behind the first (and for a long period, only) museology course in the country; its record up to recent times; its two curricula and their relation to the contemporary educational system as well as with respect to its subjects. We also study the museum's historical development from its beginnings until today. Those first approaches to our subject showed us that Museology lacks a clear epistemological foundation. Again, those manifold visions have allowed us to develop adequate concepts and categories in order to establish those foundations. We have then ordered the domain of knowledge that pertains to Museology and from that ordering we have extracted methodological principles related to similar constructs within a Philosophical Anthropology. With the help of concepts taken from the Philosophical Anthropology of Jolif, we have finally been able to give a foundation to our methodological principles, therefore allowing Museology to be developed in a sufficiently sound way so that we can even propose a college-level curriculum or our discipline out of that foundation, and such that we can finally look at Museology as a research domain with an interdisciplinary foundation.